Ascending needles in a haystack? The heterogeneous political participation effects of associational involvement by education - Hadziabdic, Sinisa (Frontiers in Sociology, 2025)
Relying on the data of the Swiss Household Panel, the paper examines the extent to which active involvement in different types of voluntary associations can bridge the political participation gap between individuals with different levels of education. Descriptive analyses reveal that individuals with higher levels of education are significantly more likely to be involved in all types of associations (expressive, instrumental, advocacy). The same education gap holds for all forms of political engagement (attitudinal, institutional, protest, community-oriented, individual). While education acts as a gateway mechanism that affects the likelihood of becoming affiliated with an association, the propensity to actively engage in associational activities after joining is largely independent of education. A longitudinal approach controlling for time-invariant endogeneity shows that active associational involvement increases almost all forms of political engagement. Due to their lower political participation prior to joining, these positive effects are in most cases more pronounced for individuals with low qualifications. Thus, most types of associations effectively reduce the educational gap in political participation. This is particularly true for those forms of participation that are most congruent with associational activities, such as membership in political parties and community-based voluntary work. Political engagement gains are higher among highly educated members only under certain circumstances. This happens either in associational contexts where internal responsibilities are skewed in their favor, as in the case of environmental and charitable organizations, or where the raison d’être of the association implies homogeneous educational qualifications, as in the case of exclusive sports clubs and specific trade unions. Individualized forms of political participation, such as boycotts, are the forms of engagement least affected by the collective action that takes place in associations. Taken together, these empirical findings suggest that associations are an often neglected channel of social mobility, mitigating political differences between social classes and thus promoting social cohesion. At the same time, they offer a more nuanced view, emphasizing that not all associations are capable of bridging the political capital of different social classes and that not all political attitudes are malleable enough to be modified.